Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Problem Based Learning dengan Media Powtoon di Kelas V SDN 21 Tanjung Bonai Aur Kabupaten Sijunjung - Suslianti, Rani; Masniladevi, Masniladevi; Waldi, Atri; Fitria, Yanti (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to describe the improvement of student learning outcomes in Pancasila Education learning using the Problem Based Learning Model with Powtoon Media in Class V SDN 21 Tanjung Bonai Aur, Sijunjung Regency. This research is a Class Action Research (PTK) that uses qualitative and quantitative approaches. Two cycles were carried out, namely cycle I consisting of 2 meetings and cycle II consisting of I meetings. Data collection techniques are in the form of observation, test, and non-test. The results of this study show an increase in the teaching module of the first cycle with an average percentage of 89.58% with good qualifications (B) and increased in the second cycle to 95.83% with excellent qualifications (SB). Implementation in the aspect of teachers in the first cycle with an average percentage of 85.71% with good qualifications (B) and increased in the second cycle to 96.42% with very good qualifications (SB), in the aspect of students in the first cycle with an average percentage of 85.71% with good qualifications (B) and increased in the second cycle to 96.42% with very good qualifications (SB). The learning outcomes of students in the first cycle with an average percentage of 74.89% and increased in the second cycle to 89.16%. Based on these results, it can be concluded that using the Problem Based Learning (PBL) model with Powtoon media can improve the learning outcomes of Pancasila Education in students.